Radiological malunion after ankle fractures in older adults: definitions and new thresholds derived from clinical outcome data from the AIM trial. (12th October 2022) - Knight, Ruth; Keene, David J.; Dutton, Susan J.; Handley, Robert; Willett, Keith
Abstract : Aims: The rationale for exacting restoration of skeletal anatomy after unstable ankle fracture is to improve outcomes by reducing complications from malunion; however, current definitions of malunion lack confirmatory clinical evidence. Methods: Radiological (absolute radiological measurements aided by computer software) and clinical (clinical interpretation of radiographs) definitions of malunion were compared within the Ankle Injury Management (AIM) trial cohort, including people aged ≥ 60 years with an unstable ankle fracture. Linear regressions were used to explore the relationship between radiological malunion (RM) at six months and changes in function at three years. Function was assessed with the Olerud-Molander Ankle Score (OMAS), with a minimal clinically important difference set as six points, as per the AIM trial. Piecewise linear models were used to investigate new radiological thresholds which better explain symptom impact on ankle function. Results: Previously described measures of RM and surgeon opinion of clinically significant malunion (CSM) were shown to be related but with important differences. CSM was more strongly related to outcome (-13.9 points on the OMAS; 95% confidence interval (CI) -21.9 to -5.4) than RM (-5.5 points; 95% CI -9.8 to -1.2). Existing malunion thresholds for talar tilt and tibiofibular clear space were shown to be slightly conservative; new thresholds which better explain function were identified (talar tilt > 2.4°; tibiofibular clear space > 6 mm). Based on this new definition the presence of RM had an impact on function, which was statistically significant, but the clinical significance was uncertain (-9.1 points; 95% CI -13.8 to -4.4). In subsequent analysis, RM of a posterior malleolar fracture was shown to have a statistically significant impact on OMAS change scores, but the clinical significance was uncertain (-11.6 points; 95% CI -21.9 to -0.6). Conclusion: These results provide clinical evidence which supports the previously accepted definitions. Further research to investigate more conservative clinical thresholds for malunion is indicated. Cite this article: Bone Jt Open 2022;3(10):841–849.